Self-management of cardiac pain in women: an evidence map. Issue 11 (25th November 2017) - Parry, Monica; Bjørnnes, Ann Kristin; Clarke, Hance; Cooper, Lynn; Gordon, Allan; Harvey, Paula; Lalloo, Chitra; Leegaard, Marit; LeFort, Sandra; McFetridge-Durdle, Judith; McGillion, Michael; O'Keefe-McCarthy, Sheila; et al.
Abstract : Objective: To describe the current evidence related to the self-management of cardiac pain in women using the process and methodology of evidence mapping. Design and setting: Literature search for studies that describe the self-management of cardiac pain in women greater than 18 years of age, managed in community, primary care or outpatient settings, published in English or a Scandinavian language between 1 January 1990 and 24 June 2016 using AMED, CINAHL, ERIC, EMBASE, MEDLINE, Proquest, PsychInfo, the Cochrane Library, Scopus, Swemed+, Web of Science, the Clinical Trials Registry, International Register of Controlled Trials, MetaRegister of Controlled Trials, theses and dissertations, published conference abstracts and relevant websites using GreyNet International, ISI proceedings, BIOSIS and Conference papers index. Two independent reviewers screened using predefined eligibility criteria. Included articles were classified according to study design, pain category, publication year, sample size, per cent women and mean age. Interventions: Self-management interventions for cardiac pain or non-intervention studies that described views and perspectives of women who self-managed cardiac pain. Primary and secondary outcomes measures: Outcomes included those related to knowledge, self-efficacy, function and health-related quality of life. Results: The literature search identified 5940 unique articles, of which 220 were included in the evidence map. Only 22% (n=49) were intervention studies. Sixty-nine per cent (n=151) of the studies described cardiac pain related to obstructive coronary artery disease (CAD), 2% (n=5) non-obstructive CAD and 15% (n=34) postpercutaneous coronary intervention/cardiac surgery. Most were published after 2000, the median sample size was 90 with 25%–100% women and the mean age was 63 years. Conclusions: Our evidence map suggests that while much is known about the differing presentations of obstructive cardiac pain in middle-aged women, little research focused on young and old women, non-obstructive cardiac pain or self-management interventions to assist women to manage cardiac pain. PROSPERO registration number: CRD42016042806 .